O PAPEL DO ENFERMEIRO NA AMPLIAÇÃO DA COBERTURA VACINAL DO HPV: DESAFIOS E ESTRATÉGIAS EM SAÚDE PÚBLICA - Abrantes Ferreira, Gilmara; do Nascimento Andrades Feitosa, Ankilma; Quental , Ocilma Barros de; Feitosa, Marcelo de Oliveira (Brazilian Journal of Implantology and Health Sciences, 2024)
Vaccination against the human papillomavirus is an essential strategy for preventing virus-related cancers, such as those of the cervix, penis, and anus. Nurses play a critical role in all stages of immunization, including storage, administration, and guidance. However, adherence to vaccination programs has been hindered by misinformation and public resistance. Thus, this study aims to investigate the role of nurses in expanding vaccination coverage against human papillomavirus, focusing on challenges and strategies in public health. It is an integrative literature review, with studies sourced from electronic databases, including the Virtual Health Library, Scientific Electronic Library Online, Google Scholar, and PubMed. The findings highlight that nurses play not only a relevant but also an imperative and strategic role in increasing human papillomavirus vaccination coverage. This expansion faces challenges involving both the community and public health services, requiring nurses to develop and implement strategies to overcome these obstacles, thereby ensuring effectiveness and equity in healthcare services. Low adherence to vaccination remains a challenge in primary care, linked to various factors such as fears about vaccine efficacy and potential side effects, doubts regarding its importance, and the misconception that vaccination might encourage early sexual activity and discourage the use of other preventive methods. Nurses assume an indispensable role in virus prevention efforts, acting as key agents in educational initiatives targeting parents and adolescents. In primary care, their role is crucial in raising awareness about the severity of the infection, its potential complications, and the importance of widespread vaccination.